Ibn al-Quff on preventive medicine - Wan Mohd Zuferi , Wan Nadzlia Shazwanie; Shuriye, Abdi Omar (IIUM Press, 2011)
This chapter studies Ibn AI-Quffs' contributions to preventive medicine. The main focus is to provide answers on Ibn AI-Quffs concepts of medical regulations, dietetics and diagnoses. The chapter also focuses on Ibn AI-Quffs work entitled Jami' al-Gharad. In fact, this book is devoted to preventive medicine, hygien and healing arts. The methodology adopted in this chapter is library based research and data is collected from reliable sources. The significance of this chapter is that it studies the efforts ofIbn AI-Quff on the subject